Anarchitextures: Intermedial Encounters On The Screen - Mikou, Ariadne (The International Journal of Screendance, 2017)
In this article I draw on architectural and choreographic ways of thinking to discuss how filmed material is transformed through projection and active and mobile spectatorship. Shifting my attention from what is projected to where it is projected, I expand the discourse beyond the single flat cinematic screen. I do this by concentrating on how the projected surface (its placement in space and its assembly with multiple screens) creates social encounters. This study accepts Rosenberg's definition of the screen as "a receptor of an otherwise ephemeral image and which reifies that image in the process of receiving it." Anarchitextures is a screen-based performance project through which I explored Eisensteinian montage to include a spatial and ambulatory practice. The project speaks to choreographic environments and events that use the screen as a socially engaged practice, and also poses some questions regarding the boundaries that appear to shape the screendance field.